Cybersecurity integration in distance learning: an analysis of student awareness and attitudes - Adnan Hnaif; Areej Mofeed Derbas; Sally Almanasra (Institute of Advanced Engineering and Science, 2024)
With the rapid growth of distance learning, especially since the COVID-19 pandemic, cybersecurity has become increasingly essential to protect students, instructors, and institutions from cyber threats. This paper examines the role of cybersecurity in enhancing students’ security awareness during distance learning. A literature review covers critical cyber threats in distance learning and strategies to mitigate risks through cybersecurity tools, policies, training, and promoting a culture of cybersecurity. Primary research was conducted by surveying 531 university students engaged in distance learning to assess their cybersecurity awareness, attitudes, and behaviors. Results indicate relatively low awareness and adoption of secure practices. Recommendations include implementing multi-layered cybersecurity defenses, student security awareness training, and nurturing a “human firewall” through a cyber-aware campus culture. Cyber risks can be reduced through proactive partnerships between students, faculty, information technology (IT) staff, and administrators to secure distance learning environments.